2017
DOI: 10.1080/16546628.2017.1389208
|View full text |Cite
|
Sign up to set email alerts
|

Salivary proteome and glucose levels are related with sweet taste sensitivity in young adults

Abstract: Sweet taste plays a critical role in determining food preferences and choices. Similar to what happens for other oral sensations, individuals differ in their sensitivity for sweet taste and these inter-individual differences may be responsible for variations in food acceptance. Despite evidence that saliva plays a role in taste perception, this fluid has been mainly studied in the context of bitterness or astringency. We investigated the possible relationship between sweet taste sensitivity and salivary compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…There is additional evidence of an association between other salivary metabolites and sensory perception. These include an inverse association between salivary glucose and sweet sensitivity [120], although this was only found in female participants, and a similar relationship between salivary urea and bitter taste sensitivity in renal disease participants [121]. While glucose tastes sweet and urea tastes bitter, it is unlikely salivary levels would approach the concentrations necessary to be perceptible and directly mask exogenous tastants [122,123].…”
Section: Potential Physiological Significance Of Salivary Metabolitesmentioning
confidence: 99%
“…There is additional evidence of an association between other salivary metabolites and sensory perception. These include an inverse association between salivary glucose and sweet sensitivity [120], although this was only found in female participants, and a similar relationship between salivary urea and bitter taste sensitivity in renal disease participants [121]. While glucose tastes sweet and urea tastes bitter, it is unlikely salivary levels would approach the concentrations necessary to be perceptible and directly mask exogenous tastants [122,123].…”
Section: Potential Physiological Significance Of Salivary Metabolitesmentioning
confidence: 99%
“…Salivary proteins such as proline-rich proteins (PRPs) [11,12] and cystatins [13,14] levels have been linked to different levels of perception and acceptance of astringent foods and beverages. Also, salivary carbonic anhydrase VI, cystatins and PRPs have been linked to the intensity of bitterness perception [15][16][17] and amylase, carbonic anhydrase VI and cystatins seem to be linked to sweet taste sensitivity [18]. Knowing how saliva varies in response to stimulants can be useful to understanding how they may modify subsequent food perception, information that can be used in nutrition programmes or in the catering and hotel industry.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a trend has been shown between bitter sensitivity and saliva interferon-α (53) , two specific basic PRP (54) , amylase fragments, immunoglobulins and serum albumin and/or serum albumin fragments, cystatin SN (55) , gustin (carbonic anhydrase VI) gene polymorphism, salivary zinc and BMI in human subjects (29) . Finally, a relationship between salivary leptin levels and bitter perception dependent on sex and BMI was found by Rodrigues et al (44) . Actually, it has been suggested that sex and BMI variables might influence saliva composition which may affect bitter taste response (44) .…”
Section: The Role Of Saliva In Taste Perception: Bitternessmentioning
confidence: 71%
“…Finally, a relationship between salivary leptin levels and bitter perception dependent on sex and BMI was found by Rodrigues et al (44) . Actually, it has been suggested that sex and BMI variables might influence saliva composition which may affect bitter taste response (44) .…”
Section: The Role Of Saliva In Taste Perception: Bitternessmentioning
confidence: 71%